Embolization of splenic artery aneurysms using coils and n‑butyl 2-cyanoacrylate (NBCA) with a newly developed polytetrafluoroethylene (PTFE)-coated microcatheter: A case series of 3 patients - Kenichi Ito, MD; Hiroki Kamada, MD, PhD; Sota Oguro, MD, PhD; Koyo Kondo, MD; Taishi Furukawa, MD; Hiroyuki Sakakibara, MD, PhD; Kei Takase, MD, PhD (Radiology Case Reports)
This retrospective case series evaluates an alternative embolization technique for splenic artery aneurysms (SAA) using a combination of coils and NBCA delivered through a Carry Leon NSX microcatheter, addressing the challenge of unpredictable NBCA behavior in high-risk aneurysms. Three female patients—a 55-year-old, a 60-year-old, and an 80-year-old—presented with SAAs that were either incidentally discovered or demonstrated significant growth over time, prompting intervention due to the potential risk of rupture. Each patient underwent successful embolization via a triple coaxial system that allowed precise coil placement and controlled NBCA injection, resulting in complete aneurysm occlusion with minimal complications such as mild splenic infarction or transient inflammatory responses. These cases demonstrate that the use of a PTFE-coated NSX microcatheter can enhance the safety and efficacy of NBCA injections, reduce the number of coils required, and simplify the embolization procedure, suggesting a promising advancement in the management of visceral arterial aneurysms.